Influência do uso de diferentes irrigantes finais na ultraestrutura da dentina radicular – estudo in vitro - Tissiani, Luanda (2019)
This study aimed to evaluate, in vitro, the influence of the use of different final irrigants on the dentin ultrastructure. Six extracted bovine single-rooted teeth were used for the present study. After removal of the dental crown, root remnants measuring 15 mm in length were obtained. Two longitudinal grooves were made on the buccal and lingual surfaces, along the entire length of the remaining root, and two circular grooves at 5 mm and 10 mm from the apex, using a diamond disc. The chemical-mechanical preparation was performed with distilled water and K-type files, manually enlarging up to #50 file. The 6 samples were randomly divided into three groups of 2 samples each, according to the final irrigant used for a period of 30 seconds, as follows: G1 – distilled water (control group), G2 – EDTA 17%, G3 – QMIX. After the final irrigation protocols, the samples were irrigated with 5 ml of distilled water and cleaved in all the grooves previously made, providing 4 samples per group (n=4), using only the middle third for evaluation. The evaluation of the dentin ultrastructure was carried out in sections obtained in ultramicrotomy by means of transmission electronic microscopy, considering the following classification status: intact, dispersed and altered. As this is a qualitative assessment, only a descriptive analysis of the images obtained was carried out. The results showed that group 1 (control) kept the structure intact, while group 2 (EDTA) and group 3 (QMix) caused its dispersion. It can be concluded that the tested final irrigants do not change the dentine ultrastructure and only promote its dispersion.